Lowering BaTi2O5 Curie temperature by Sr facile hydrothermal ion-exchange while retaining the original particle morphology - Miyazaki, Hidetoshi; Yamashita, Yosuke; Yamada, Katsumi; Kubota, Takeshi; Omata, Kohji; Tsukada, Shinya (Materials chemistry and physics, 2021)
Ti-peroxo iso-poly acid solution was prepared by dissolving metal Ti in an aqueous NH3/H2O2 solution, and the obtained Ti-peroxo iso-poly acid and Ba(OH)2 solutions were reacted and heat-treated at 1000 °C to obtain BaTi2O5 particles. Subsequently, the hydrothermal treatment of the obtained BaTi2O5 particles in an aqueous Sr(NO3)2 solution was carried out at 200 °C for 24 h to synthesize Sr-substituted BaTi2O5 particles. The resulting Sr-substituted BaTi2O5 particles retained the crystal structure and microstructure of the source BaTi2O5 particle, and Sr0.025Ba0.975Ti2O5 and Sr0.042Ba0.968Ti2O5 powders were obtained with the precursor aqueous Sr(NO3)2 solution having concentrations of 0.5 and 1.0 mol/L, respectively. Raman spectroscopy was conducted to characterize the obtained BaTi2O5 and Sr-substituted BaTi2O5 particles, and the Curie temperature of the source BaTi2O5, Sr0.025Ba0.975Ti2O5 and Sr0.042Ba0.958Ti2O5 powders was 480, 460, and 430 °C, respectively. From the results, it was clarified that Sr-substituted BaTi2O5 particles can be easily synthesized in a wide composition range by a hydrothermal treatment, and the Curie temperature of BaTi2O5 can be controlled by the amount of the Sr substitution quantity. •Substitution of Sr for Ba in the BaTi2O5 particles was carried out by hydrothermal treatment.•The composition of the obtained SrxBa1-xTi2O5 was confirmed by XRD (evaluation of cell volume) and XRF measurement.•The Curie temperature (observed by Raman measurement) of the specimen decreased with increasing the x in SrxBa1-xTi2O5.